Inflation and counter-inflationary policy measures: The case of Germany - Andrew Watt (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2022)
Germany has suffered an inflationary shock broadly commensurate with that of the Euro Area as a whole, with energy playing a slightly larger, food a somewhat smaller than average role. Because of differences in consumption patterns, the current inflationary surge hits low-income households significantly harder than wealthier ones. In addition, exposure to gas heating, which cuts across income brackets, is an important factor. So far nominal wage increases in response to the price shock have been very muted, with no sign of a price-wage spiral. Policymakers have responded to the crisis with three large packages of increasing size and breadth. The overall stabilisation effect of the measures cannot be quantified ex ante (because it depends on price developments) but will likely represent around two-thirds of the shock. While the packages are judged positively overall, a number of criticisms can be raised. The initial response was hesitant. Not until the autumn were more radical measures, including a gas and electricity price brake announced. Overall, targetting of the measures in favour of vulnerable households has been limited. A number of measures - including the gas price brake, unless last-minute changes are made - benefit wealthier households more than their poorer counterparts in absolute terms. Other measures incentivise higher, rather than lower fossil-fuel consumption. Germany did not come up with a formalised "social pact" to address the crisis, although high-level tripartite discussions were held. Implicit coordination can be made out, however, in which government measures encourage the collective-bargaining parties to limit the pass through of higher current inflation into nominal wages.
urn:nbn:de:101:1-2023011911331022061022
Keywords: 330; AK Wien; Germany; Inflation; gas; electricity; price cap; HICP; energy; distribution; social pact; real wages